Comparison of core and surface cultures in recurrent tonsillitis - Bista, M.; Sinha, B.K.; Amatya, R.C.M.; Tuladhar, N.R.; Pokharel, B.M. (Journal of Institute of Medicine Nepal, 2007)
This prospective study was done to find out the most common organism affecting the tonsils in recurrent tonsillitis and to compare the microorganisms found in the core and surface of such tonsils. A total of 50 patients attending ENT Out patient Department of Tribhuvan University Teaching Hospital (TUTH) from February 2000 to August 2001 were included in the study. All these patients had undergone tonsillectomy under general anaesthesia by dissection method. Among these 39 patients had undergone tonsillectomy for recurrent tonsillitis and 11 had undergone tonsillectomy for reasons other than recurrent tonsillitis. The excised tonsils were kept in agar plates and transported to the microbiology laboratory within half an hour of surgery. The culture was taken fromthe surface and the core after cutting the tonsils into half by a sterile blade and with another sterile blade only core was extracted in a wedge shaped manner and was cultured in aerobic (5% sheep blood agar, Chocolate agar and McConkey’s agar and anaerobic (gas pack jar system) media for 24 - 48 hours. The most common microflora seen in recurrent tonsillitis was Streptococcus viridans from the surface, as well as the core. Other common micro organisms prevalent on the surface in recurrent tonsillitis were Staphylococcus aureus, and Brahmnella catarrhalis. Likewise other common micro organisms in the core in recurrent tronsillitis were Staphylococcus aureus, Klebsiella pneumonie, and Haemophillus influenzae. There was no statistical difference between the micro organisms found on the surface and the core except for Brahmnella catarrhalis which was significantly more on the surface. Anaerobes were isolated only from the core and there was no statistical difference between the micro organisms isolated from the non-infected tonsils and from recurrent tonsillitis Journal of Institute of Medicine Vol.27(3) 2005